Project-based learning in teaching speaking to young learners: Is it effective? - Elok Widiyati; Wulan Pangesti (EduLite: Journal of English Education, Literature and Culture, 2022)
Students’ disfluency in speaking is caused by limited practice, incorrect pronunciation, and inappropriate learning methods. That of the last point drove this research in finding out the effectiveness of using Project-based Learning (PBL) to improve students’ speaking skills. The study participants were 59 students of the seventh graders of SMP Muhammadiyah 1 Kudus, divided into the experimental and the control classes using a quasi-experimental research design. The data were obtained from the pre-test and the post-test. The results showed that the students’ speaking ability mean scores in both classes were higher in the post-test than in the pre-test. In addition, the independent sample t-test supported the result in the hypothesis testing. It means that project-based learning applied had a significant difference or effective to improve young-learner students’ speaking skills. To conclude, using this method created more fun, active, and interactive speaking class atmosphere for young learners.